Doped nanoparticles for optoelectronics applications - Godlewski, M.; Wolska, E.; Yatsunenko, S.; Opalińska, A.; Fidelus, J.; Łojkowski, W.; Zalewska, M.; Kłonkowski, A.; Kuritsyn, D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Nanoparticles of wide band gap materials doped with transition metal ions or rare earth ions are intensively studied for their possible applications in a new generation of light sources for an overhead illumination. In this work we discuss mechanisms of emission enhancement in nanoparticles doped with rare earth or/and transition metal ions. Arguments are presented that phosphors of nanosize may emit light more efficiently and thus be applied in practical optoelectronic devices.